Risk assessment and modelling: IITA - Tamo, Manuele; Beed, Fenton D.; Goergen, Georg E.; Hanna, R.; Coyne, D.; Asten, Piet J.A. van; Legg, James P. (International Potato Center, 2012)
Recent and current efforts at IITA to assess risks due to the various biotic stresses, arthropod pests and diseases, are presented for different cropping systems. In the case of cassava arthropod pests, the focus is on temperature-mediated interactions between the pest and its natural enemy which has been introduced to keep the former under control.